Reinventing the perspective of rural education based on dialogue with ancestral knowledge: a reading from the perspective of Southern Epistemologies. - Lucila Leal da Costa Araújo; Sérgio Roberto Moraes Corrêa (Revista Brasileira de Educação do Campo)
This article presents partial results of a Master's degree in Education research project (currently in its final stages), which focuses on the school curriculum in quilombola communities in the Amazon, focusing on the advances and limitations of the recognition of ancestral territories. For the purposes of this article, we address the contributions of the ancestral knowledge of rural peoples to the reinvention of rural education in the Amazon, using Epistemologies of the South as a theoretical framework for dialogue. The article aims to analyze how the knowledge of historically subalternized groups can challenge hegemonic curricular logics and contribute to the construction of intercultural and democratic pedagogical practices. This is a qualitative study, using the state of knowledge as a methodological strategy. This initial literature review indicates a growing academic interest in ancestral knowledge in the educational field, although structural challenges persist to its valorization in school curricula and in Brazilian society. The study reinforces the need for public policies and pedagogical practices that recognize and engage with these knowledges and other ways of life, expanding the visibility of education for rural, water, and forest peoples, committed to critique and emancipation.